Three-dimensional pin forces during rowing at three different stroke rates - Loschner, C.; Smith, R. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The forces acting on the boat are the drag force, stretcher force, pin force, buoyancy force, and the weight force. These forces determine the acceleration of the boat in three dimensions. Maintaining the highest and least variable boat velocity in the direction of progression is a goal of competitive rowing. The pin force is a major contributor to the net boat force especially during the drive phase and each of the propulsive, transverse and vertical pin forces have an effect on the instantaneous boat velocity. Oar handle force, usually the normal force, has been a regular target for measurement by researchers. While helpful information is available from recording the handle force, the longitudinal force on the oar is entirely neglected. Full decomposition of the oar force on the pin into the propulsive, transverse and vertical forces would provide a more complete picture of the effect of pin forces in all three directions.